DIRECTIONS FOR IMPROVING THE ORGANIZATION OF TOURISTIC-RECREATIONAL ACTIVITIES IN THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
In this article, the touristic-recreational opportunities of the Fergana Valley and their geographical features, territorial aspects of the touristic-recreational potential are studied and appropriate conclusions are drawn. In addition, recommendations were made on ways to improve the organization of touristic and recreational activities.